2022
DOI: 10.3168/jds.2021-20979
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonication as a novel processing alternative to pasteurization for camel milk: Effects on microbial load, protein profile, and bioactive properties

Abstract: Ultrasonic technology presents a promising novel tool in the food industry for the processing of milk and dairy products. In this study, we investigated the effects of ultrasonication (US) as an alternative to thermal pasteurization for stabilization of the bioactive properties of camel milk. Camel and bovine milk samples were subjected to US at 6 different power levels (US1-US6), and 1 set of each type of milk was concurrently subjected to flash heat pasteurization (FHP) for comparative analysis (100 mL; n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…In addition, Dhahir et al (2020a) investigated the effects of US on the milk-borne microorganisms (E. coli O157: H7 and S. Typhimurium) and several components in camel milk and found that US treatment for 15 min significantly reduced the microbial load of these two bacteria, and US did not show detrimental effects on the composition of fatty acids, lipid peroxides, and protein fractions. Recently, Mudgil et al (2022) investigated the influences of US treatments on microbial load, protein compositions, and bioactive properties of camel milk and reported that US at >160 W for 10 min could realize a microbial safety for public consumption without affecting its bioactive properties, such as antioxidative capacity and cholesterol esterase inhibition.…”
Section: Ultrasonication Treatment For Goat Milkmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Dhahir et al (2020a) investigated the effects of US on the milk-borne microorganisms (E. coli O157: H7 and S. Typhimurium) and several components in camel milk and found that US treatment for 15 min significantly reduced the microbial load of these two bacteria, and US did not show detrimental effects on the composition of fatty acids, lipid peroxides, and protein fractions. Recently, Mudgil et al (2022) investigated the influences of US treatments on microbial load, protein compositions, and bioactive properties of camel milk and reported that US at >160 W for 10 min could realize a microbial safety for public consumption without affecting its bioactive properties, such as antioxidative capacity and cholesterol esterase inhibition.…”
Section: Ultrasonication Treatment For Goat Milkmentioning
confidence: 99%
“…Recently, Mudgil et al. (2022) investigated the influences of US treatments on microbial load, protein compositions, and bioactive properties of camel milk and reported that US at >160 W for 10 min could realize a microbial safety for public consumption without affecting its bioactive properties, such as antioxidative capacity and cholesterol esterase inhibition.…”
Section: Fundamentals and Developments Of Nonthermal Milk Processingmentioning
confidence: 99%